2020
DOI: 10.1002/adfm.202003217
|View full text |Cite
|
Sign up to set email alerts
|

SAM Functionalized ZnO Nanowires for Selective Acetone Detection: Optimized Surface Specific Interaction Using APTMS and GLYMO Monolayers

Abstract: In modern days, self‐assembled monolayer (SAM) functionalized surfaces represent an interesting tool for the development of ultrasensitive and selective sensing platforms for the detection of chemical substances such as biomolecules and gases. The ability of SAM to generate different functional groups on a single surface such as zinc oxide (ZnO) can be used to immobilize biomolecules and detect different analytes such as gases, proteins, etc. Herein, SAM functionalized ZnO NW‐based sensors are developed for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 44 publications
(60 reference statements)
0
60
0
Order By: Relevance
“…The inset in Figure 6 a, demonstrating the difference between O 1s spectra taken in O 2 and O 2 /EtOH atmospheres, shows an increase in oxygen signal in the 531.5–533 eV region. In this region, the oxygen signals from different hydrocarbons containing oxygen, H 2 O and OH usually appear [ 42 ]. Similar signal increases can be observed in the case of O 2 /EtOH/H 2 O and O 2 /MeCHO atmospheres.…”
Section: Resultsmentioning
confidence: 99%
“…The inset in Figure 6 a, demonstrating the difference between O 1s spectra taken in O 2 and O 2 /EtOH atmospheres, shows an increase in oxygen signal in the 531.5–533 eV region. In this region, the oxygen signals from different hydrocarbons containing oxygen, H 2 O and OH usually appear [ 42 ]. Similar signal increases can be observed in the case of O 2 /EtOH/H 2 O and O 2 /MeCHO atmospheres.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction of the gassensing response in humid environment for SMOX-based gas sensors is due to the competition of adsorption between the analyte gas and the water molecules as reported earlier. 8,37 Figure 3g and Figure S5b 3g). The sensor fabricated with SnO 2 -SiO 2 /60 CSNWs shows the best response among all the fabricated sensors.…”
Section: Gas Sensing Propertiesmentioning
confidence: 96%
“…The calibration curves, response vs concentration follow a typical power-law relation (in agreement with the eq 3) for SMOX-sensors, further confirming the absence of any saturation process. 8,37 The sensors detection limit is calculated while considering the minimum response value of 1 in eq 3. The values of different parameters calculated by the power-law fits are summarised in Table S2.…”
Section: Gas Sensing Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To this light, Kim et al and Singh et al demonstrated an exceptional acetone sensitivity (refer to Table 1 ) of Co 3 O 4 NPs modified SnO 2 NWs and self-assembled monolayer (SAM) functionalized ZnO NWs [ 70 , 71 ]. These sensory materials can be synthesized via vapor–liquid–solid (VLS), sol–gel, and thermal annealing processes to detect acetone with an LOD of 0.5 ppm.…”
Section: Diverse Nanostructures In Acetone Detectionmentioning
confidence: 99%